2013
DOI: 10.2355/isijinternational.53.96
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Normalizing Processes on Microstructure and Impact Toughness in Ti-bearing Weld Metal of Multilayer MAG Welded HSLA Steel

Abstract: The influences of different normalizing heat treatments on microstructure, non-metallic inclusions and impact toughness in MAG Ti-bearing weld metal of HSLA steel has been studied. It has been shown that for the Ti-bearing weld metal the impact toughness after normalizing treatment decreases significantly against prolonging holding time and increasing normalizing temperature. The Mn-depleted zone forms around the Ti-bearing phase (MnTiO3) precipitated on Mn-Si oxide. Proeutectoid ferrite preferentially nucleat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Ductile cast iron (DCI) 1,2) has attracted attention as a material that can replace welded joints. 3) In our previous experimental study, the authors revealed that the fatigue strength of DCI joints is about 2 times or more larger than that of non-load-carrying cruciform welded joints. 4) Hereafter, non-load-carrying cruciform welded joint is referred to welded joint or cross welded joint.…”
Section: Introductionmentioning
confidence: 95%
“…Ductile cast iron (DCI) 1,2) has attracted attention as a material that can replace welded joints. 3) In our previous experimental study, the authors revealed that the fatigue strength of DCI joints is about 2 times or more larger than that of non-load-carrying cruciform welded joints. 4) Hereafter, non-load-carrying cruciform welded joint is referred to welded joint or cross welded joint.…”
Section: Introductionmentioning
confidence: 95%